Functional Outcome of Patients with Proximal Humerus Bone Tumors after Tikhoff–Linberg Procedure and Reconstruction Using Hemiarthroplasty in a National Orthopaedic Hospital (2020–2023) - Khrisna Purwa Satyaksa; Mujaddid Idulhaq (Universitas Airlangga, 2026)
Background: The proximal humerus is a common site for primary and metastatic bone tumors. Limb-salvage surgery aims to achieve oncologic clearance while preserving function. The Tikhoff–Linberg procedure combined with hemiarthroplasty is one reconstructive option; however, functional outcomes remain variable. This study aimed to evaluate functional outcomes following this procedure at a tertiary orthopaedic center.Methods: A retrospective observational study was conducted on patients who underwent Type I Tikhoff –Linberg resection with hemiarthroplasty for proximal humerus tumors at Prof. Dr. R. Soeharso National Orthopaedic Hospital between January 2020 and December 2023. Functional outcomes were assessed using the Disabilities of the Arm, Shoulder and Hand (DASH) and Musculoskeletal Tumor Society (MSTS) scores at a minimum follow-up of 6 months.Results: Eleven patients met the inclusion criteria (6 males, 5 females; mean age 51.2 years). Four patients (36%) had benign tumors and seven (64%) had malignant tumors. The mean DASH score was 42.3, and the mean MSTS score was 15.4. Patients with benign tumors demonstrated better functional outcomes (DASH 39.4; MSTS 17.6) compared to those with malignant tumors (DASH 46.9; MSTS 13.2). Shoulder range of motion was limited, particularly in flexion and abduction, although distal upper limb function was preserved.Conclusion: Tikhoff–Linberg resection with hemiarthroplasty provides acceptable functional outcomes, particularly in terms of hand and elbow function. However, shoulder mobility remains limited. Careful patient selection is required based on functional demand and prognosis.